Subalternity in Amitav Ghoshs Sea of Poppies: Representation of Indian Womens Struggle Against Patriarchy - SOPHIA KIKI ARTANTI (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2019)
This study analyses the subaltern that represented by Deeti in Amitav Ghosh’s Sea of Poppies. The subject of the subaltern as an Indian woman is struggling against patriarchy in society. This study uses the postcolonialism theory, including the theory of subaltern to analyze the representation of the subaltern subject who fights against patriarchy. That subject represented by Indian women as the subject of the subaltern. The narration of Deeti in the first Trilogy Sea of Poppies by Amitav Ghosh is the main focus of this study. This study using postcolonialism theory from Homi K. Bhabha and Gayatri Chakravorty Spivak, then subaltern theory also using Gayatri Chakravorty Spivak which describes how colonialized subject lives and theories from Sylvia Walby and Gerda Lerner for the definition of patriarchy. So, this study mainly about how patriarchy will be related to Deeti as the subaltern explained by Gayatri Chakravorty Spivak. The data will be taken from many aspects such as dialogues, a depiction of the situation, characters, etc. This study analyzed two problems, which are (1) How is subalternity represented in Amitav Ghosh’s Sea of Poppies? (2) How do Indian Women’s struggle to fight against patriarchy in Sea of Poppies by Amitav Ghosh? The results of this study show that Subaltern represented by Indian Women. Then the struggle of Deeti as an Indian Woman and the other characters fights against the patriarchy. Keywords: Postcolonialism, Subaltern, Patriarchy